Pathological Unit for Specific New Mucinous Benign Pancreatic Cysts - Hilendarov, A.; Velkova, K.; Siracov, N.; Tchervenkov, L.; Georgiev, Al. (Highlights on Medicine and Medical Science Vol. 15, 2021)
Introduction: The cystic lesions of the pancreas include a variety of pathologies that can be broadly classified as neoplastic and non-neoplastic cysts. A new non-neoplastic cystic lesion known as mucinous non-neoplastic cyst (MNC) has recently been described. Materials and Methods: The histological assessment of the diagnosis was done using imaging (ultrasound and CT) methods as well as invasive procedures. Eleven examples of pancreatic cystic lesions were given, all of which were discovered by ultrasonography and computed tomography while being used for other purposes. Results and Discussion: A 26-33 mm cyst was discovered in the body of the pancreas, apparently communicating with the pancreatic duct. Endoscopic Retrograde Cholangiopancreatography and laboratory tests of liver function, serum CEA, and carbohydrate antigen C19 -9 were all normal. Six patients had a simple cyst lined with mucinous epithelium after a distal pancreatectomy.Under two years of surveillance, the other five cases have not changed in size and structure. Conclusion: Due to the inability to completely confirm the benign nature of the lesions, we recommend that patients diagnosed with 'benign' mucinous neoplasm be closely monitored. Furthermore, the MNC's existence as a truly unique cystic lesion remains debatable.